Laser trackers for large-scale dimensional metrology: A review - Muralikrishnan, Bala; Phillips, Steve; Sawyer, Daniel (Precision engineering, 2016)
•The paper reviews laser tracker literature as applied to large-scale dimensional metrology.•Ranging technology, absolute distance measurement, targets and hand-held accessories are surveyed.•Geometrical error models and compensation procedures are discussed.•Improvements to measurement accuracy through multi-station measurements are presented.•Performance evaluation test procedures, documentary standards, uncertainty, and traceability issues are discussed. Thirty years since their invention, laser trackers are now recognized as the measurement tool of choice in the manufacture and assembly of large components. The general design of laser trackers, i.e., a ranging unit on a two-axis gimbal, has not changed significantly over the years. However, innovations in ranging technology, for example, the emergence of increasingly accurate absolute distance meters (ADMs), are providing users with an alternative to interferometers (IFMs). Hand-held accessories such as touch probes and line scanners are expanding the scope and applicability of laser trackers. In this paper, we survey the literature in all areas of laser trackers as applied to large-scale dimensional metrology (LSDM), with emphasis on error modeling, measurement uncertainty, performance evaluation and standardization.